Neotype Designation for the Marine Flatworm, Acanthozoon alderi (Polycladida: Cotylea: Pseudocerotidae), from India with Comments onthe Taxonomical Status of the Genus - Sudhanshu Dixit (2018)
Acanthozoon alderi is an ovoid, medium-sized pseudocerotid. Body margin ruffled; pseudotentacles black and pointed, with white tips. Dorsal surface covered with papillae, except for the cerebral region. Background colour light brown, with marbled blackish pattern, middorsal black band with white blotches; black submarginal band and marginal white rim. This species was described from Borneo; however, no type specimen was designated or deposited in any museum by the author. Many nomenclature problems and misidentification have been encountered with this species (it has been identified as Acanthozoon sp. in many instances). Thus, it is necessary to designate a neotype to solve the problems of doubtful and confusing identities and maintain nomenclature stability. The present paper details internal anatomy for the first time and makes important observations about the nominal status of the genus.